Modernisasi dan Transformasi Kembali ke Tradisi: Fenomena Ngaben di Krematorium bagi Masyarakat Hindu di Bali - I Gde Pitana (Pusat Kajian Bali Universitas Udayana, 2020)
Conducting cremation ceremony (ngaben) in crematorium among Balinese Hindus is relatively a new phenomenon, pioneered by Maha Gotra Pasek Sanak Sapta Rsi, the biggest maxima-clan in Bali. This maxima-clan constructed a crematorium called Santhayana in 2008. The number of cremation ceremony conducted in Crematorium Santhayana increases over time, mainly due to the practical values and efficiency, compared to conducting the ceremony conventionally in one’s own village. The more affordable cost and the less intensive communication with the village of origin are yet additional reasons, especially for those residing outside Bali. By employing participant-observation and in-depth interviews in data collection, analysed qualitative-interpretively, this research confirmed Giddens’ Structuration theory, that as duality, structure is both constraining and enabling the actors. On the other hand, actors’ patterned activities will develop new structure. However, it is interesting in the case of cremation in crematorium Santhayana, that the transformation toward modernity is by making use of traditional reference, i.e. old lontar, named Yama Purana Tatwa.